Effect of Stud Connector Diameter on the Behavior of Steel–Lightweight Self-Compacting Concrete Composite Beams with Partial shear Connection - Bayadir Abed Hadi; Samoel Mahdi Saleh (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the efficacy of using lightweight self-compacting concrete (LWSCC) in steel-concrete composite beams, focusing on the role of headed stud connectors in shear connection. The research aimed to evaluate the behavior and shear strength of M16 and M20 headed stud connectors within LWSCC. To this end, six push-out test samples and six simply supported steel-LWSCC composite beams were fabricated and tested, with variables including the degree of shear connection (DSC) and stud diameter. The results demonstrated that an increase in DSC significantly enhanced the ultimate load capacity, service load, and stiffness of the composite beams, with marked improvements observed in the beams with M16 connectors (94%, 95%, and 122%, respectively) and those with M20 connectors (43%, 43%, and 20%, respectively). Furthermore, increasing the stud diameter from 16mm to 20mm resulted in a 38% increase in shear strength of the connectors and notably improved the mechanical characteristics of the beams. The study also found that while an increased DSC reduces deflection at ultimate and service loads due to heightened stiffness, a larger stud diameter has only a marginal effect on deflection. This research highlights the potential of LWSCC in enhancing the structural performance of steel-concrete composite beams, particularly with optimized shear connections, offering valuable insights for advancements in construction materials and methods. Highlights : Enhanced Load Capacity: Increase in the degree of shear connection significantly boosts ultimate load capacity and stiffness in composite beams. Stud Diameter Impact: A 38% rise in shear strength is achieved by increasing stud diameter from 16mm to 20mm. Deflection Reduction: Higher degree of shear connection effectively minimizes deflection, though stud diameter has minimal impact. Keywords : Lightweight Self-Compacting Concrete, Steel-Concrete Composite Beams, Shear Connection, Headed Stud Connectors, Structural Performance.